2016
DOI: 10.1186/s12879-016-1967-3
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of TB treatment in HIV co-infected TB patients in Ethiopia: a cross-sectional analytic study

Abstract: BackgroundTB and HIV are the most prevalent communicable diseases of major public health importance in the populations of sub-Saharan African countries, and an estimated 30 % of HIV infected persons have dual infection with TB. TB is the leading cause of death in HIV infected individuals, and HIV co-infected TB patients have multiple individual, disease specific and treatment related factors that can adversely affect their treatment outcomes. There is lack of evidence on the individual patient outcomes of HIV … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

14
49
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 8 publications
14
49
6
1
Order By: Relevance
“…At the same time, our findings are from one site, while the national data is countrywide and thus disparity is likely. However, similar findings to the present study have also been reported by other studies conducted in Ethiopia [28][29][30].…”
Section: Discussionsupporting
confidence: 81%
“…At the same time, our findings are from one site, while the national data is countrywide and thus disparity is likely. However, similar findings to the present study have also been reported by other studies conducted in Ethiopia [28][29][30].…”
Section: Discussionsupporting
confidence: 81%
“…This result is unsatisfactory when compared with the WHO report, where 73% of TB/HIV co-infected patients globally, and 75% in Africa achieved successful treatment 12. The success rate of this study is a lot lower than previous works in resource limited countries 1416,18. The low rate of successful treatment outcomes found in our study might be partly due to the high rate of transferred patients (46.3%), where treatment outcomes of those patients were not recorded in the facility where they started the treatment.…”
Section: Discussioncontrasting
confidence: 74%
“…The high rate of mortality in this study might be partly due to improper selection of anti-TB medication in patients who had a prior history of TB treatment where a five-drug combination must be used,11 while in the study area among patients who were candidates for rifampicin, isoniazid, ethambutol, pyrazinamide, and streptomycin, five patients received rifampicin, isoniazid, ethambutol, and pyrazinamide instead. Previously conducted studies showed varying results with regard to mortality of TB/HIV co-infected patients, ranging from 1.8% to 29% 1416,18,23,27. Mortality is different with geographical location and the year at which the studies were conducted.…”
Section: Discussionmentioning
confidence: 99%
“…13 In the study of Ali et al out of the total TB patients enrolled in the study, proportion of HIV non-infected patients were higher to that of HIV co-infected. 16 In our study the prevalence of TB-HIV co-infection is found to be 7.28%. They found that, treatment success rate was somewhat lower i.e.…”
supporting
confidence: 45%